What's Happening in Leadership? - Australian Learning and Teaching Council (Australian Learning and Teaching Council (ALTC), 2010)
This document provides information on the leadership projects of the Australian Learning and Teaching Council (ALTC). The Leadership for Excellence in Learning and Teaching Program aimed to strengthen leadership and build the capacity to lead change for the future enhancement of learning and teaching in Australian higher education. The program has several different strands, focusing on the institutional, discipline-based and specific project levels. The three priority areas are institutional leadership, disciplinary/cross-disciplinary, and consolidated leadership outcomes. As with all attempts at classification, there are projects that are not as clearly identified with the priority area as others. Projects addressing the third priority area build on outcomes from other projects funded under priorities one and two, and are listed under these first two priorities.